Ophthalmologic Drug Guide - Rhee, Douglas J. (Springer New York : Imprint: Springer, 2011)
The updated edition of this popular pocket guide includes new drugs available and FDA-approved since publication of the first edition and also guidance on using the growing number of drugs now prescribed for off-label purposes, such as anti-VEGF agents, used in cancer treatments, which are also being used to stop cell growth in age-related macular degeneration. Drugs are grouped by presenting disease (e.g., glaucoma, retinal disease, cataracts), and readers may also access information via the Product Index or the Subject Index. The entire book is presented in a table format to facilitate quick look-up.